The incidence of overeducated and undereducated worker for manufacturing sector in Malaysia - Jamaludin, Salwaty; Safian, Sharulshahida Shakrein; Said, Rusmawati; Muhamed, Ariff Azly (Human Resource Management Academic Research Society, 2022)
This study measures educational mismatch – overeducated and undereducated by aggregating individual mismatch for each group of occupations for manufacturing sector in Malaysia. This is crucial as the incidence of mismatch in the labour market could affect the workers’ salaries and wages, and impede long-term country’s’ productivity. By employing Realised Matches method on Malaysia Labour Force Survey (LFS) data, the findings concluded that the population of undereducated workforce outweighed the population of overeducated workforce for manufacturing sector, with 36% of the workforce being undereducated compared to the latter at 14% of the workforce. However, a pattern was identified indicating an increase in the overeducated workforce throughout the year, implicating that those of the overeducated workforce (underemployed) were increasing.